Dependence of spring wheat seed productivity on mineral fertilizer doses and seeding rates - D. A. Kuznetsov; G. N. Ibragimova (Аграрная наука Евро-Северо-Востока)
The article presents the results of field studies conducted in 2018-2020 on the leached chernozem of the Volga foreststeppe. The objects of the research are the varieties of spring wheat Tulaykovskaya 10 (control), Yoldyz and Tulaykovskaya 108. At seeding rates of 5.0 and 5.5 million viable seeds per 1 ha the effect of mineral fertilizers was studied. The fertilizers were represented by a complete NPK mineral fertilizer of 16 kg a.i. and by top-dressing with mineral nitrogen fertilizer in the tillering phase at the doses of 30, 60 and 90 kg a.i./ha against this background. An increase in the seeding rate of seeds from 5.0 to 5.5 million seeds per 1 ha led to a significant increase in the yield of spring wheat in all years of study (by 0.11-0.26 t/ha), the weight of 1000 seeds – by 1.44 g (LSD05 = 1.14), the nature of grain - by 8 g/l (LSD05 = 5). The effect of top-dressing with nitrogen fertilizers has been proved – the increase in yield ranged from 0.15 to 0.28 t/ha over three years on the average, the maximum from a dose of 60 kg a.i. A statistically significant increase in the weight of 1000 seeds was provided by nitrogen fertilization in doses of 60 and 90 kg a.i./ha – by 2.79 and 1.87 g, respectively (LSD05 = 1.47), grain nature increased at doses of 30, 60 and 90 kg a.i./ha by 34, 23 and 16 g/l, respectively (LSD05 = 2). The average yield of spring wheat varieties with the selected combination of factors (5.5 million seeds/ha, N60) was in the range of 2.64-2.70 t/ha with a mass of 1000 grains 44.03-44.56 g, the nature of grain 765-783 g/l. The studied varieties differed in responsiveness to nitrogen fertilization (N60 against the NPK background): Tulaykovskaya 10 (+0.43 t/ha), Tulaykovskaya 108 (+0.39 t/ha), Yoldyz (+0.24 t/ha). Increases in yield from an increase in the seeding rate were 0.20 (Yoldyz), 0.25 (Tulaykovskaya 108) and 0.26 t/ha (Tulaykovskaya 10). In general, according to the experiment relative to the control variety Tulaykovskaya 10, the variety Yoldyz stood out with a stable increase in yield over the years of research (+0.08 t/ha), statistically significant in years with insufficient moisture. The Yoldyz variety was distinguished by an increased profitability of cultivation – up to 59.4 % at a seeding rate of 5.5 million viable seeds/ha against the background of applying mineral fertilizers N16P16K16 for pre-sowing soil cultivation.